Biogas Dung Production: Community Participation Bangkro and Changhaitok Sub-District, Pattani Province - Tansom, Ubol; Paothong, Somphop; Soontornnon Sinchai , Piyasiri; Muhamud, Nisaporn (Area Based Development Research Journal, 2020)
Reducing household expenses and recycling remains a constant challenge in the villages and community. Bangkro and Changhaitok sub-district communities, Khokpho district, pattani province addressed the challenge using community participation by producing biogas from dung. From 2017 to 2019, 40 farming families in Bangkro and Changhaitok sub-district, Khokpho district, Pattani province participated in this study and developed 1,200 liters of biogas digester. Research knowledge transfer training is operated and expanded to the community by transferring biogas production from dung technology to farmers’ groups. The community uses the floating drum digester form to build a biogas digester. It is found that farmers use biogas as renewable energy in household gas in order to reduce cost of living and liquefied petroleum gas for 1,680 – 3,360 baht/year. Additionally, the sludge can be taken from gas fermentation pond for agricultural purposes. Economically, it can reduce household cost for 1,800-3,600 baht/year and reduce global warming, the environmental impact and dung-related health problems in the community. Finally, the local farmers are able to form a group to establish a learning hub for biogas production to those who are interested.